PHI-base in 2022: a multi-species phenotype database for Pathogen–Host Interactions. Issue Volume 50:Issue D1(2022) (12th November 2021) - Urban, Martin; Cuzick, Alayne; Seager, James; Wood, Valerie; Rutherford, Kim; Venkatesh, Shilpa Yagwakote; Sahu, Jashobanta; Iyer, S Vijaylakshmi; Khamari, Lokanath; De Silva, Nishadi; Martinez, Manuel Carbajo; Pedro, Helder; et al.
Abstract: Since 2005, the Pathogen–Host Interactions Database (PHI-base) has manually curated experimentally verified pathogenicity, virulence and effector genes from fungal, bacterial and protist pathogens,  which infect animal, plant, fish, insect and/or fungal hosts. PHI-base (www.phi-base.org ) is devoted to the identification and presentation of phenotype information on pathogenicity and effector genes and their host interactions. Specific gene alterations that did not alter the  in host  interaction phenotype are also presented. PHI-base is invaluable for comparative analyses and for the discovery of candidate targets in medically and agronomically important species for intervention. Version 4.12 (September 2021) contains 4387 references, and provides information on 8411 genes from 279 pathogens, tested on 228 hosts in 18, 190 interactions. This provides a 24% increase in gene content since Version 4.8 (September 2019). Bacterial and fungal pathogens represent the majority of the interaction data, with a 54:46 split of entries, whilst protists, protozoa, nematodes and insects represent 3.6% of entries. Host species consist of approximately 54% plants and 46% others of medical, veterinary and/or environmental importance. PHI-base data is disseminated to UniProtKB, FungiDB and Ensembl Genomes. PHI-base will migrate to a new gene-centric version (version 5.0) in early 2022. This major development is briefly described.